Hematologic, Biochemical, and Endocrine Parameters in Horses With Tooth Resorption and Hypercementosis. (September 2017) - Earley, Edward T.; Rawlinson, Jennifer R.; Baratt, Robert M.; Galloway, Stephen S.; Smedley, Rebecca C.; Scarlett, Janet M.; Refsal, Kent R.; Dotzel, Allison. R.; Cox, Victor. S.; Perkins, Gillian A.
Background: Equine odontoclastic tooth resorption and hypercementosis (EOTRH) is a frequently diagnosed condition in adult horses. The underlying etiology is still unknown. Hematologic, biochemical, and endocrine values have not been reported in EOTRH-affected horses. Objectives: The main objective of the study was to describe the hematologic, biochemical, and endocrine parameters in horses with EOTRH. Study Design: Descriptive cross-sectional study of client-owned animals with EOTRH. Methods: A complete blood count, biochemistry panel, and endocrine profile were performed in horses diagnosed with EOTRH. Diagnosis was based on oral and radiographic examination findings and confirmed with histopathology. Results: Eighteen horses with EOTRH aged 10 to 32 years from various regions of the United States were sampled. The only consistent abnormality on the complete blood cell count and chemistry panel was hypoalbuminemia (88%). Endocrine parameters demonstrated no major abnormalities in the functioning of the thyroid and pituitary pars intermedia. The parathyroid hormone concentration was increased in 7 (47%) of 15 horses with an elevated 25-hydroxy vitamin D in 3 (17%) of 17 horses. Main Limitations: The main limitations of this study are the small sample size and lack of age-matched and management-matched control horses. Conclusions: The relevance of elevated parathyroid hormone in this study cannot be determined due to the lack of age-based controls and large population studies. With the small population evaluated in this study, there are no obvious hematological, biochemical, and endocrine changes evident. Further evaluation with signalment-matched controls will be necessary to evaluate some trends noted in the laboratory values.